Diffuse neonatal hemangiomatosis presenting as congestive heart failure - Sheetal Agarwal; Anu Sharma; Arti Maria (Mattioli1885, 2017)
Diffuse neonatal hemangiomatosis is a rare condition with a very high mortality rate if left untreated. We report a neonate having around 490 cutaneous and multiple diffuse liver hemangiomas presenting as congestive heart failure. Prompt treatment was instituted with decongestive drugs and prednisolone for anticipated life threatening complications due to hepatic hemangiomas. Propranolol was added later as it is known to precipitate congestive failure and also to avoid long-term complications of steroids. The child responded well. However, there is no consensus regarding the initial line of management, which needs to be individualized keeping in mind the efficacy, long-term side effects of the drug and the clinical presentation.